2020
DOI: 10.35808/ijeba/447
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ownership’s Concentration Moderating Dividend Policy Effects on Firm Value

Abstract: Purpose: The main aim of this research is to examine the role of ownership's concentration moderating of dividend policy effects on firm value. Design/methodology/approach: For the empirical part we have used a sample of 23 companies with five years of observation a total of 115 data observations. The retrieval of data observations in the sample was based on certain criteria in the period of 2014-2018. Findings: The result supported the hypothesis that dividend policy had a positive effect on firm value. Besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Research implemented by Sari & Subardjo (2022), explained that dividend policy has a positive effect on the value of the company. These results are in line with research conducted by Zulfikar et al (2020); Janah & Ariani (2022), which explains that dividend policy has a positive effect on the value of the company based on relative value. However, different results obtained from the study by Nirawati et al (2022), stated that dividend policy has a negative effect on the value of the company based on relative value.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Research implemented by Sari & Subardjo (2022), explained that dividend policy has a positive effect on the value of the company. These results are in line with research conducted by Zulfikar et al (2020); Janah & Ariani (2022), which explains that dividend policy has a positive effect on the value of the company based on relative value. However, different results obtained from the study by Nirawati et al (2022), stated that dividend policy has a negative effect on the value of the company based on relative value.…”
Section: Introductionsupporting
confidence: 91%
“…The announcement of dividend distribution by the company is a positive signal for investors to earn profits. The results of this study are in line with research conducted byZulfikar et al (2020);Irawan et al (2022), which states that dividend policy has a positive effect on the value of the company based on relative value.4 ConclusionThe results showed that environmental performance, managerial ownership, and dividend policy have a positive effect on the relative value of the company, which means that the results of this study are consistent with legitimacy theory, agency theory, and signaling theory. Companies that manage their environmental activities well will get a positive response from investors because good environmental performance will also improve public perception of the company, and hence, increase the relative value of the company.…”
supporting
confidence: 90%
“…An interesting contribution of our study is to test whether the impact of ownership structure and CEO duality change during a crisis period. Moreover, another major contribution is to test, like Zulfikar et al (2020) and Ngatno et al (2021), using an interaction variable, the moderating effect of the crisis period on the association between both the degree of ownership concentration and DDP on the one hand, and between the CEO duality and DDP on the other.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, insofar as CEO duality and ownership concentration vary significantly over time, this study aims to empirically study the effects of both CEO duality and ownership concentration on DDP. Furthermore, like Zulfikar et al (2020) and Ngatno et al (2021), we test, using an interaction variable, the moderating effect of the crisis period on the association between both the degree of ownership concentration and the DDP on the one hand, and between the CEO duality and the DDP on the other.…”
Section: Introductionmentioning
confidence: 99%
“…Yulianto et al [ 3 ] argue that corporate governance and dividend policy can mitigate the agency problems resulting from ownership structure, thereby increasing firm value. Zulfikar et al [ 4 ] believe that the concentration of ownership weakened the relationship between dividend policy and firm value in Indonesia market. However, much less is known about how continuous cash dividends affect the relation between ownership structure and firm value in China.…”
Section: Introductionmentioning
confidence: 99%